Pacaran or Ta’aruf: Contesting Two Cultural Trends of Mate Selection in Indonesia - Sidiq Hari Madya (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
In Indonesia, marriage still serves the only legal institution of family formation. However, at least since 1950s, the pattern of mate selection to expectedly end up in marriage has undergone a silent transformation from the traditional arranged to self-choice. Following the transition, two major cultural trends termed: pacaran and ta’aruf rise as popular ways of young Indonesian Muslims finding their life partner. This study would examine how the changing pattern of mate selection took place in Indonesia and how, under an influence of Giddens’ modernization theory, increasing cultural trends of mate selection were elaborated. Ethnographic evidence provided by previous research was presented. Current trends of mate selection were discussed. The analysis incorporated dimensions of family relations and gender differences to see how much those two aspects influenced the process of spouse choice in Indonesia. The study found that the two most-contested ideals of spouse choice in Indonesia were adopted from ‘traditions’ already existing in other part of the world. However, in the modern Indonesian context, to fully understand how these two emerge and currently contested cannot by simply mentioning a process of globalization without taking into account a complex social and political policy happening particularly during the last century.